Identifying the factors influencing the development and application of cloud computing to enhancement of efficiency of education - Kavoosi Ghafi, Arman; Moradi, Behdad; Shafiabadi, Mohammad Hossein; Torkashvand, Fatemeh (International journal of industrial engineering and operational research, 2024)
The purpose of the present research is to identify the factors affecting the development and application of cloud computing in order to increase the efficiency of education. The research method is qualitative-quantitative exploratory. The sample size is 272 people. For data analysis, structural equation modeling and exploratory factor analysis were used using SPSS-v21, Smart Pls-v2 and Lisrel-v8 software and Grenard theory. The results obtained in the proposed model showed that among the 16 available indicators for the application and development of cloud computing, five main components are identifiable: the development of a training system tailored to the organization's development, updating, and educational system, obtaining necessary licenses and using cloud computing specialists. Out of the 43 extracted indicators, three main components were identified for training efficiency, which include individual, educational and complex components.